Regiospecific three-component access to fluorescent 2,4-disubstituted quinolines via one-pot coupling-addition-cyclocondensation-sulfur extrusion sequence - Rotzoll, Sven; Willy, Benjamin; Schönhaber, Jan; Rominger, Frank; Müller, Thomas J. J. (European journal of organic chemistry, 2010)
2,4-Di- and 2,4,7-trisubstituted quinolines are readily synthesized in a regioselective fashion from acyl chlorides, terminal alkynes, and 2-aminothiophenols by a consecutive, microwave-assisted one-pot three-component Sonogashira coupling-Michael addition-cyclocondensation sequence and following sulfur extrusion in moderate to good yields. The terminal sulfur extrusion step was studied by DFT computations. The absorption spectra of 2,4-disubstituted quinolines can be rationalized by DFT-ZINDO-CI calculations and all derivatives show intense blue emission upon UV excitation.
Dedicated to Prof. Dr. Franz Effenberger on the occasion of his 80th birthday
Gesehen am 22.06.2023